2013
DOI: 10.3389/fnana.2013.00013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural examination of the corticocollicular pathway in the guinea pig: a study using electron microscopy, neural tracers, and GABA immunocytochemistry

Abstract: Projections from auditory cortex (AC) can alter the responses of cells in the inferior colliculus (IC) to sounds. Most IC cells show excitation and inhibition after stimulation of the AC. AC axons release glutamate and excite their targets, so inhibition is presumed to result from cortical activation of GABAergic IC cells that inhibit other IC cells via local projections. However, it is not known whether cortical axons contact GABAergic IC cells directly. We labeled corticocollicular axons by injecting fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…An important proviso to this interpretation is that it is difficult to distinguish between terminals and fibers using this technique, raising the possibility that the anterograde signals seen in the central nucleus were passing fibers. Since then, multiple studies using modern tracers and electron microscopy have found clear evidence for CC terminals in the CNIC in rats, cats, gerbils, guinea pig and ferrets (Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998; Bajo and Moore 2005; Bajo et al 2007; Nakamoto et al 2013), though generally in lower numbers than in other regions of the IC. In cats, the strongest projections to the central nucleus, come intriguingly from nontonotopic areas of dorsal and intermediate, part of the posterior ectosylvian gyrus.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…An important proviso to this interpretation is that it is difficult to distinguish between terminals and fibers using this technique, raising the possibility that the anterograde signals seen in the central nucleus were passing fibers. Since then, multiple studies using modern tracers and electron microscopy have found clear evidence for CC terminals in the CNIC in rats, cats, gerbils, guinea pig and ferrets (Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998; Bajo and Moore 2005; Bajo et al 2007; Nakamoto et al 2013), though generally in lower numbers than in other regions of the IC. In cats, the strongest projections to the central nucleus, come intriguingly from nontonotopic areas of dorsal and intermediate, part of the posterior ectosylvian gyrus.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…This was based on physiological findings that CC inputs inhibited sound-induced IC responses (Massopust Jr and Ordy 1962; Amato, La Grutta and Enia 1970). However, electron microscopy of labeled CC synapses in the DC, LC and CNIC all showed asymmetric terminals, and the presence of small round vesicles in CC synaptic boutons that are indicative of excitatory synapses (Saldaña, Feliciano and Mugnaini 1996; Nakamoto et al 2013). In addition, lesioning of the CC system depressed synaptic release of labeled aspartate, further suggesting that these projections are glutamatergic (Feliciano and Potashner 1995).…”
Section: Molecular and Circuit-level Considerationsmentioning
confidence: 99%
See 3 more Smart Citations